On Niccolò Machiavelli : the bonds of politics - Pedullà, Gabriele (Core knowledge (Columbia College (Columbia University)), 2023)
Gabriele Pedullà-a leading Italian expert and acclaimed writer-provides a vivid and engaging introduction to Machiavelli's life and works that sheds new light on his originality and relevance.